Challenges of Energy Saving Crisis as a Panacea to Hybrid Electric Vehicle (HEV) - Orie, Chukwulenwenwa John; Nwatu, Queendalline Ijeoma (Richtmann Publishing, 2011)
Modern HEVs make use of efficiency-improving technologies energy such as regenerative braking, which convertsthe vehicle's kinetic energy into battery-replenishing electric energy, rather than wasting it as heat energy as conventional brakesdo. Some varieties of HEVs use their internal combustion engine to generate electricity by spinning an electrical generator (thiscombination is known as a motor-generator), to either recharge their batteries or to directly power the electric drive motors. ManyHEVs reduce idle emissions by shutting down the ICE at idle and restarting it when needed; this is known as a start-stop system.A hybrid-electric produces less emissions from its ICE than a comparably-sized gasoline car, since an HEV's gasoline engine isusually smaller than a comparably-sized pure gasoline-burning vehicle (natural gas and propane fuels produce lower emissions)and if not used to directly drive the car, can be geared to run at maximum efficiency, further improving fuel economy.